2021
DOI: 10.1021/acs.analchem.1c00431
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Raman Spectra by Using Deep Learning Methods in the Identification of Marine Pathogens

Abstract: The need for efficient and accurate identification of pathogens in seafood and the environment has become increasingly urgent, given the current global pandemic. Traditional methods are not only time consuming but also lead to sample wastage. Here, we have proposed two new methods that involve Raman spectroscopy combined with a long short-term memory (LSTM) neural network and compared them with a method using a normal convolutional neural network (CNN). We used eight strains isolated from the marine organism U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 62 publications
1
41
1
Order By: Relevance
“…In their 2012 publication, Stöckel et al showed an apparent correspondence between relationships established by Raman spectroscopy and phylogenetic or taxonomic relationships of Bacillus species [ 18 ]. Predictions of genetic relatedness are also possible via Raman spectroscopy and machine learning [ 19 ]. However, the phylogenetic relationship of some species may not always match Raman spectroscopic similarity.…”
Section: Resultsmentioning
confidence: 99%
“…In their 2012 publication, Stöckel et al showed an apparent correspondence between relationships established by Raman spectroscopy and phylogenetic or taxonomic relationships of Bacillus species [ 18 ]. Predictions of genetic relatedness are also possible via Raman spectroscopy and machine learning [ 19 ]. However, the phylogenetic relationship of some species may not always match Raman spectroscopic similarity.…”
Section: Resultsmentioning
confidence: 99%
“…54,55 Particularly, LSTM networks are the most effective solution to sequence learning 56 and have been recently applied to analyzing Raman spectral data. 25,57,58 LSTM networks are an improved version of RNNs, which are explicitly designed to avoid the long-term dependency problem. LSTM generally comprises four main gates, i.e., the input gate, the forget gate, the output gate and the cell state.…”
Section: Discussionmentioning
confidence: 99%
“…Bidirectional input flows in two directions, making a Bi-LSTM network preserve the future and past information. In a previous study, 1,200 data points of the Raman spectrum were directly input into the LSTM network, which caused 800 epochs of training ( Yu et al, 2021 ). Excessive training epochs will lead to overfitting of the model.…”
Section: Discussionmentioning
confidence: 99%
“…A long short-term memory (LSTM) network is a novel recurrent neural network (RNN) architecture in conjunction with an appropriate gradient-based learning algorithm ( Yu et al, 2021 ). Unlike RNN networks, the LSTM network has a hidden inner state that enables applying the previous sequence input to a later calculation and avoids gradient disappearance through a gating unit system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation